“Making Noise” with Comics: An Interview with Argentine Author, Artist, Singer, and Song Writer, Isol - Jennifer Nagtegaal (Comicalités)
The following interview with Marisol Misenta, known professionally as Isol, discusses a number of ways in which the award-winning author, musician, and occasional comics artist from Argentina brings together music, singing, and narration through images in what she calls “una poción para soñar” (a concoction to dream about). The interview focuses on the so-called “discomic” Novela gráfica (Graphic Novel), released in 2014 by the Buenos Aires-based band SIMA, for which Isol served as lead vocalist, but also touches on some of the Argentine artist’s more recent collaborative and interdisciplinary art projects and performances. Topics include patterns in the relationship between comics and sound, the role of the reader-listener in experiencing and experimenting with the hybridization of music and comics with the discomic object, and how together comics and music (and sound by extension) enhance the audience experience.